Spotlight on Cloud : Becoming Cloud Native with Jon Collins - Collins, Jon (O'Reilly Media, Inc., 2019)
Startups seem to come out of nowhere, disrupting their markets and leaving traditional organizations to ask themselves how they too can adopt cloud-centric models and approaches. But just how realistic is this? Today's enterprises are sometimes criticized for legacy thinking, but they also have to bear the burden of infrastructure, supply chains, security, governance frameworks, and customer drivers that can't be changed at the flick of the switch. Here's the good news: enterprise concerns and cloud native principles may be better aligned than you think. Flexible infrastructure is becoming a staple of modern data centers. Microservices models align with software architecture best practices, while Agile innovation approaches such as DevOps are maturing in governance. At the same time, cybersecurity and risk management is an area of traditional strength, and operational principles used in the enterprise are as important as ever. Find out how businesses can adopt cloud native principles without throwing away what it means to be an enterprise. Recorded on May 2, 2019. See the original event page for resources for further learning. Find future live events to attend or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Cloud, you'll learn about the complex, ever-evolving world of the cloud. You'll discover how successful companies have adopted and embraced this massive network of shared information and how you can follow their lead to transform your organization and prepare for the Next Economy.